IMPACT OF DOUBLE LAYER UNLOCKED SUTURE VS SINGLE LAYER LOCKED SUTURE IN PREVENTION OF CAESAREAN SCAR ISTHMOCELE – RANDOMISED CONTROLLED TRIAL AT A TERTIARY CARE CENTRE IN MAHARASHTRA. - Dr. Neethika Raghuwanshi; Dr. Guramrit Kaur (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
ABSTRACT Background: The increasing rates of cesarean sections (CS) have led to a rise in complications such as cesarean scar defects, which can manifest as niches or thinning of the residual myometrium, potentially resulting in postmenstrual spotting, chronic pelvic pain, and other serious conditions. Optimal uterine closure techniques are critical for preventing these defects, but evidence comparing single-layer locked versus double-layer unlocked sutures is limited. Thus, the current study was conducted to assess compare the impact of single layer locked versus double layer unlocked suture. Methodology: This randomized controlled trial was conducted at a tertiary care center over 18 months, enrolling 300 women undergoing their first cesarean section. Participants were randomly assigned to either single-layer locked sutures (Group A) or double-layer unlocked sutures (Group B). Follow-up was performed at six months using transvaginal sonography to assess the presence of cesarean scar defects and residual myometrial thickness. Results: Group A demonstrated a higher need for additional sutures, increased bleeding rates, and a greater need for blood transfusions compared to Group B. At the six-month follow-up, Group A had a higher incidence of niches, significantly lower residual myometrial thickness, and narrower adjacent myometrial thickness compared to Group B. These findings align with other studies suggesting that double-layer unlocked sutures may provide better outcomes. Conclusion: The double-layer unlocked suture technique is more effective than the single-layer locked technique in preventing cesarean scar isthmocele and promoting better uterine scar healing. It resulted in lower prevalence and narrower width of niches, better preservation of residual myometrial thickness, and greater adjacent myometrial thickness, making it a preferable choice for cesarean deliveries.